Dua Dekade Trend Penelitian Kewarganegaraan Digital: Analisis Bibliometrik Database Scopus (2004-2024) - Aprilianata, Aprilianata; Mahendra, Wisnu; Ramadhan, Idang (Journal of Moral and Civic Education, 2025)
Over the past few decades, digital citizenship has become an increasingly important subject of academic research. This article aims to identify research trends on digital citizenship based on the Scopus database. This study uses 215 documents searched in the Scopus database and uses bibliometric analysis techniques with RStudio and VOSviewer. From the results of the analysis, it can be concluded that from 2004 to 2024 there has been a 24.19 percent increase in digital citizenship research. The affiliations that produce the most research are The Ohio State University, University of North Carolina Charlotte, Near East University, Universitas Muhammadiyah Surakarta, and the University of Missouri. Meanwhile, the author with the highest number of citations is Moonsun Choi from The Ohio State University. The words media literacy, digital citizenship education, teachers, and professional digital competence are recommended keywords that are widely used when conducting research on the topic of digital citizenship. Future research is expected to provide a more substantial contribution in formulating policies and practical actions that support the formation of good citizens.